Internet, prestação de contas e transparência na gestão pública municipal - De Moraes, Nelson Russo [UNESP]; Gomes, Wilson Da Silva; Porto Júnior, Francisco Gilson Rebouças; De Moraes, Dorival Russo (My University, 2015)
This article deals with the employment of general public administration and municipal specific way, does the internet to publish their accountings. The phenomenon of implementation of internet happened when the company sought ways to strengthen democracy through increased participation of civil sphere in political decision. In this sense, the study takes into account the so-called crisis of participation that affected the democratic legitimacy of the contemporary state, examining possible paths for the resumption of the participatory interest of society in policy decisions. An important path to the conceptual organization of this work was the study of the laws that compel the government to advertising and the use of the internet as a tool for serving the information and checks and balances as a way of meeting the legal requirements established by the Brazilian Federal Constitution 1988. well to analyze the universe of Brazilian municipalities impacted by the legislation, established a sample of 57 (fifty seven) municipalities whose official websites were researched by means of targeted navigations. Finally, we observe that the municipalities are still in search of efficient and consolidation to make public their accounts through the worldwide network of computers process.
Internet, accountability and transparency in municipal management
Keywords: Democracy; Internet; Law on transparency in public management; Public management; The fiscal responsibility law